Modelling, analysis, and implementation of a switched‐inductor based DC/DC converter with reduced switch current stress. Issue 8 (4th May 2021) - Sadaf, Shima; Al‐Emadi, Nasser; Iqbal, Atif; Bhaskar, Mahajan Sagar; Meraj, Mohammad
Abstract: This paper proposes a technique for switch current stress reduction in a Switched Inductor DC‐DC Boost Converter (SIBC). The proposed technique comes up with a low‐cost design, high voltage conversion ratio with a less duty cycle value, and lower current stress without increasing the component count. This topology is basically a transformer‐less design where one diode of the traditional switched inductor configuration has been replaced with a switch, which is in parallel with the existing switch, resulting in a design that can incorporate active switches with a low current rating, since the total input current is equally shared by them. The detailed modes of operation in both continuous conduction mode (CCM) and discontinuous conduction mode (DCM) and steady‐state analysis, the non‐idealities' effect on voltage gain, design approach, and a comparative study with other DC‐DC converters for some significant performance characteristics are provided. The experimental validations for the performance and working of the 500 W designed prototype are presented.